Prospect Theory, Behavioral Theory, and the Threat-Rigidity Thesis: Combinative Effects on Organizational Decisions to Divest Formerly Acquired Units - Shimizu, Katsuhiko (Academy of Management Journal, 2007)
By complementing prospect theory with organization-level behavioral theory and the threat-rigidity thesis, I study how factors unique to an organizational level can interact with the individual-level tendencies predicted by prospect theory. I tested this approach by examining organizational decisions to divest or retain formerly acquired units in a longitudinal setting. The results show that divestiture decisions are influenced by both individual- and organization-level factors that cannot be explained solely by one theory and provide a richer understanding of organizational risk-seeking behaviors.